Transformation Of Smoke-Free Family Behavior: Evaluation Of Nursing Intervention In Preventing Ari In Toddlers: Transformasi Perilaku Keluarga Bebas Asap Rokok: Evaluasi Intervensi Keperawatan Dalam Mencegah Ispa Pada Balita - Fahira, Jihan Gucci; Singcolan, Sellvine Marumpe; Ika Novita Sari (Infomasi dan Promosi Kesehatan, 2025)
Background: Acute Respiratory Infection (ARI) is an infectious disease affecting the respiratory tract and a leading cause of morbidity and mortality in toddlers. Cigarette smoke exposure, including thirdhand smoke, is a significant risk factor for ARI in children. Family health education is an important strategy in ARI prevention through behavioral and home environment changes. Objective: To analyze the effectiveness of family nursing interventions with health education approaches in preventing ARI due to cigarette smoke exposure in toddlers. Methods: This study used a descriptive case study design on Mr. J's family with two toddlers experiencing recurrent ARI. Interventions were implemented through comprehensive health education about cigarette smoke dangers, ARI prevention, and home environment modification. Data collection was conducted through in-depth interviews, observations, and medical documentation. The evaluation was performed by comparing family knowledge and behavior before and after intervention. Results: After health education intervention, there was a significant increase in family knowledge about cigarette smoke dangers (from 40% to 85%) and implementation of ARI prevention behaviors. The family implemented smoke-free policies at home, improved ventilation, and enhanced environmental hygiene. Both toddlers showed health improvement with decreased ARI episode frequency from an average of 4 times to 1 time in the last 3 months. Conclusion: Family nursing interventions with health education approaches proved effective in increasing knowledge and changing family behavior in preventing ARI due to cigarette smoke exposure in toddlers.